APPLICATIONS OF SYSTEM SIMULATON TO INTEGRATE AND MODEL VIRTUAL AND AUGMENTED REALITY - Ahuja, Ravi; Kumar, Umesh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Reality is something that we experience around us and it is present in the world in which we are living. On the contrary virtual reality is a world which is not present around us in the physical state yet we experience it by using modern day technology. Though it is not real we are still trying to make it very much similar to the real world environment so that we can interact with the real world by seeing it, hearing it, touching it, smelling it and feeling it. Though the virtual world is so fantasizing and fun to watch it should satisfy three of the following conditions: total realism, physical interaction and no boundaries. To make our virtual world more interactive we use the technology of programmable matter and claytronics. The programmable matter is the matter which consists of tiny modular robots that can change its shape accordingly and can transform from one shape to another.